PREGNANT EXERCISE INFLUENCE ON THE BABY’S BIRTH WEIGHTAND POSTPARTUM HEMORRHAGE - Siti Fatimah; M. Zen Rahfiludin; Apoina Kartini (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The benefits of exercise during pregnancy have been reported to be higher than its negative side effects. A reduction in low birth weight, a decrease in heart rate abnormalities of the baby and a decrease in excessive bleeding after 24 hours of labor are among those positive outcomes of the exercise during pregnancy. Aims: This study was meant to determine the effects of exercise during pregnancy Methods: This research was an explanatory research using cross sectional design.The research respondents were 42 mothers who was admitted to give birthinHermina Hospital. Twenty-one mothers who practiced twice a week of a combined yoga, pilates, hypnotherapy, and tai chi were recruited as a case group in this study. Mean while, 21 mothers who did not practice exercise during pregnancy were requested to participate in the control group of this study. The infants’ birth weight was weighed immediately after birth with the baby scales, and the mothers’ post-partum hemorrhage (PPH) were measured by the need bandages and blood ejected through similar toilet ≥ 500 ml. A statisticaltest used is the T-Test IndependentandMann-Whitney. Results: The results showed that the postpartum hemorrhage occurrence was less among respondents who practiced a regular exercise during pregnancy than who did not. However, there was no evidence of statistically difference between the two groups. The average of birth weight babies born to mothers who practiced a regular exercise during pregnancy was 3,418 ± 215 grams or greater as compared (2643 ± 180 grams).It showed a significant difference in birth weight between mothers who did exercise during pregnancy than mothers from other group (p = 0.001). Conclusion: In conclusion, the exercise during pregnancy has a positive impact on the birth weight of the babies.Thus, the authors suggest to all maternal and child health service providers to plan a pregnancy exercise program.